Children’s Well-being: Parental Awareness On Child Internet Addiction - Abdul Rashid Abdul Aziz; Amin Al Haadi Shafie; Mohd Azrin Mohd Nasir; Mohd Ropizam Mohamad Zainun; Warlan Sukandar; Nur A'in Mustafar (HRMARS, 2024)
International Journal of Academic Research in Business and Social Sciences Volume 14 Issue 1 Page (2242-2256)